Effect of Lens-Induced Myopia on Visual Cortex Activity: A Functional MR Imaging Study - Mirzajani, A.; Sarlaki, E.; Kharazi, H.H.; Tavan, M. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Myopia is a type of refractive error that blurs retinal image and in turn can change neural signals transferred from retina to visual cortex. The purpose of this study was to evaluate the effect of induced myopia on occipital visual cortex activity by fMRI results. MATERIALS AND METHODS: BOLD fMRI was performed in 13 emmetropic volunteers (refractive error, <±0.50D) with normal visual acuity, good binocular vision, and no history of neurologic illness. Visual stimulus was counterphasing vertical luminance sinusoidal grating with spatiotemporal frequency of 1.84 cycles per degree/8 Hz and contrast of 60%. The functional images were acquired in block design, during normal refractive state and induced myopia produced by convex noncoating plastic lenses of +1D, +3D, +5D, by using an EPI gradient-echo sequence in a 1.5T MR imaging scanner. fMRI data were processed by using FSL software. RESULTS: fMRI responses to visual stimuli demonstrated that percentage of BOLD signal intensity change and number of activated voxels within occipital visual cortex were reduced remarkably in induced myopic states of 1D, 3D, and 5D in comparison with normal refractive state; the results did not show a significant and regular decreasing trend in number of activated voxels and BOLD signal intensity change in these 3 different values of induced myopia. CONCLUSIONS: The findings suggest that induced myopia has a considerable effect on visual cortex activity, because myopia induced by lens of +1D is sufficient to change fMRI results significantly. Accordingly, it is essential to correct myopia before visual fMRI studies, even if it is at low levels. AC/PCanterior/posterior commissureANOVAanalysis of varianceBOLDblood oxygenation level–dependentEPIecho-planar imagingfMRIfunctional MR imagingFSLFunctional MR Imaging Software LibraryVEPvisual-evoked potential